(untitled) - Daly, Mary (Cambridge, U.K., 2000)
The book traces the consequences of different welfare state and social policy arrangements for women and men and the households in which they live. Mary Daly examines the British and German welfare states showing that both countries differ markedly in the measures they have instituted in various areas.
Keywords: Public welfare,Women,Income distribution,Phúc lợi công cộng; Economic conditions; Great Britain,Germany,Great Britain,Germany,Great Britain,Germany